Pengembangan Ekowisata Berbasis Hutan Desa & Sumberdaya Air di Desa Pengejaran, Kecamatan Kintamani, Kabupaten Bangli - I Wayan Sudana; I Made Mardika; Ni Made Puspasutari Ujianti; I Gusti Ayu Intan Saputra Rini; Ni Wayan Intan Pradnyawati; Ni Gusti Ayu Made Marlin Rintha Putri (Community Service Journal (CSJ), 2026)
The Pengejaran Village Forest in Kintamani District holds significant ecological, social, and cultural potential, yet it has not been optimally developed for community-based ecotourism. This Community Service Program (PKM) aims to strengthen planning, institutional capacity, and local regulations necessary for sustainable ecotourism development. The methods applied include participatory mapping, masterplan formulation, documentation of local history, BUMDes management training, and the drafting of local customary regulations (perarem). The results indicate the successful development of an ecotourism masterplan, a village history booklet, improved BUMDes managerial capacity, and a perarem draft serving as the basis for ecotourism governance. The program enhances community awareness of conservation, strengthens local governance, and creates new forest-based economic opportunities. The participatory and culture-based approach proved effective in supporting program sustainability.